Scintigraphic Pattern of Multifocal Spinal TB - Sultana, Afroja; Sultana, Nasreen; Reza, Sharmin; Islam, Urnas; Misha, Sajjad Al (Bangladesh Journal of Nuclear Medicine, 2025)
In the evaluation of inflammatory bone disease, trauma, metabolic bone disease, and benign or malignant tumors, bone scintigraphy has an important role among the diagnostic armamentarium. In the majority of cases, the scintigraphs demonstrate unifocal or multifocal increases in tracer uptake in the affected region. However, it is well known that bone scintigraphy is nonspecific and other conditions capable of producing osteoblastic response and/or increased blood flow and also osteolytic response. These may be differentiated from each other by their characteristic scintigraphic patterns and changes on skeletal radiographs. Neoplastic metastatic disease is characterized by multifocal lesions, cold lesions (central photopenic areas), affecting most frequently the central skeleton, the ribs, the vertebrae, and the pelvis. Two cases are reported in this context, where spinal tuberculosis (Pott’s disease) mimic the typical metastatic patterns of bone scan. Bangladesh J. Nuclear Med. 27(2): 301-304, 2024